On Isomorphism Between Certain Group Algebras on the Heisenberg Group - Egwe, M.E.; Bassey, U.N. (Журнал математической физики, анализа, геометрии, 2013)
Let IHn denote the (2n + 1)-dimensional Heisenberg group and let K be a compact subgroup of Aut(IHn); the group of automorphisms of IHn. We prove that the algebra of radial functions on IHn and the algebra of spherical functions arising from the Gelfand pairs of the form (K, IHn) are algebraically isomorphic. Пусть IHn обозначает (2n+1)-мерную группу Гейзенберга, а K - компактную подгруппу Aut(IHn), группу автоморфизмов IHn. Доказано, что алгебра радиальных функций на IHn и алгебра сферических функций, возникающих из пар Гельфанда вида (K, IHn), являются алгебраически изоморфными.